Gender stereotypes and contact with gay men and lesbians: The mediational role of sexism and homonegativity. (3rd May 2019) - Salvati, Marco; Piumatti, Giovanni; Giacomantonio, Mauro; Baiocco, Roberto
Abstract: This study is grounded in Allport's intergroup contact theory and Herek's sexual prejudice theory. We aimed at (a) investigating the mediational role of sexism and homonegativity on the relation between gender, age, and contact with gay and lesbian people with gender stereotypes about gay men and lesbians; and (b) replicating and corroborating the direct associations found in previous research among these variables. The present research used secondary data from a survey conducted by the Italian National Institute of Statistics and comprehending a representative sample of 5, 863 Italian adults. The results from path analysis indicated that both homonegativity and sexism partially mediated the effect of gender and age on gender stereotypes, whereas they totally mediated the effect of contact with gay and lesbian persons. Findings suggest that reducing sexist and homonegative attitudes and increasing contact with gay and lesbian people may reduce stereotypical beliefs about homosexual people.